Biochemical analysis reveals aberrant and variable Immunoglobulin M composition in Waldenström macroglobulinemia and IgM monoclonal gammopathy of unknown significance - Oskam, Nienke; Verhaar, Wouter; Ooijevaar-de Heer, Pleuni; Amaador, Karima; Derksen, Ninotska I. L.; Keijzer, Sofie; Kersten, Marie José; Streutker, Marij; Vos, Josephine M. I.; Rispens, Theo (Frontiers in Immunology, 2025)
Waldenström Macroglobulinemia (WM) is a rare B cell malignancy defined by greater than 10% infiltration of lymphoplasmacytic cells in the bone marrow (BM) and a circulating monoclonal Immunoglobulin M (IgM), while its precursor state IgM monoclonal gammopathy of undetermined significance (MGUS) has <10% BM infiltration. WM and IgM MGUS are unique amongst malignant lymphomas because symptoms and treatment indication may be caused by monoclonal IgM and not by the malignant cell infiltration. These symptoms correlate poorly with IgM levels, suggesting there may be specific biochemical properties of those pathological IgMs, yet IgM structure in IgM gammopathies has not been systematically studied. In healthy individuals, IgM circulates as a pentameric molecule that consists of five covalently linked monomers (H2L2 pairs), a joining (J-) chain and one CD5-Like (CD5L) molecule. In order to gain insight into structural variation of IgM in monoclonal IgM gammopathies, we developed and tested several assays to determine J-chain and CD5L content and polymerization state of IgM from 29 IgM MGUS and WM patients. In multiple cases, IgM was found to be (partially) devoid of J-chain, which associated with differential assembly of IgM into variably sized polymers. Moreover, we found that IgM exceeding ~5 g/L was no longer saturated with CD5L. Relative binding of polymeric Ig receptor varied by over 30-fold. Combined, in this pilot study we demonstrate that structural and functional variation in IgM of IgM MGUS and WM is common. These aberrations in IgM structure may relate to variations in clinical phenotype in IgM monoclonal gammopathies.